1994
DOI: 10.1016/0092-8674(94)90039-6
|View full text |Cite
|
Sign up to set email alerts
|

The MO15 cell cycle kinase is associated with the TFIIH transcription-DNA repair factor

Abstract: A protein kinase activity that phosphorylates the C-terminal domain (CTD) of RNA polymerase II and is associated with the basal transcription-repair factor TFIIH (also called BTF2) resides with MO15, a cyclin-dependent protein kinase that was first found to be involved in cell cycle regulation. Using in vivo and in vitro repair assays, we show that MO15 is important for nucleotide excision repair, most likely through its association with TFIIH, thus providing an unexpected link among three important cellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
354
0
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(374 citation statements)
references
References 28 publications
17
354
0
2
Order By: Relevance
“…A third component, MAT1, was demonstrated to promote the assembly of Cdk7/CycH during CAK complex formation, and to stabilize and activate the CAK complex (Devault et al 1995;Fisher et al 1995). TFIIH, consisting of CAK and six other`core' subunits (XPB, XPD, p62, p52, p44 and p34), is involved in basal transcription and phosphorylates the CTD of the largest subunit of PolII (Roy et al 1994;Serizawa et al 1995;Shiekhattar et al 1995). In the present study, we have demonstrated that CAK and the whole TFIIH complex have different substrate speci®cities for Cdks and the Analysis of TFIIH-associated kinase activity q Blackwell Science Limited CTD in in vitro kinase assays.…”
Section: Discussionmentioning
confidence: 99%
“…A third component, MAT1, was demonstrated to promote the assembly of Cdk7/CycH during CAK complex formation, and to stabilize and activate the CAK complex (Devault et al 1995;Fisher et al 1995). TFIIH, consisting of CAK and six other`core' subunits (XPB, XPD, p62, p52, p44 and p34), is involved in basal transcription and phosphorylates the CTD of the largest subunit of PolII (Roy et al 1994;Serizawa et al 1995;Shiekhattar et al 1995). In the present study, we have demonstrated that CAK and the whole TFIIH complex have different substrate speci®cities for Cdks and the Analysis of TFIIH-associated kinase activity q Blackwell Science Limited CTD in in vitro kinase assays.…”
Section: Discussionmentioning
confidence: 99%
“…The trimeric CAK complex in metazoans appears to be multi-functional; it is required for CDK activation through threonine phosphorylation in their T-loop regions (Larochelle et al, 1998;Harper and Elledge, 1998), and is also involved in the regulation of transcription both as free CAK complex and as a component of the general transcription factor TFIIH (Feaver et al, 1994;Roy et al, 1994;Serizawa et al, 1995;Shiekhattar et al, 1995;Adamczewski et al, 1996) through phosphorylation of the RNAP II CTD and a number of general and regulatory transcription factors. These include the GTFs TBP, TFIIEa, TFIIFa (Ohkuma and Roeder, 1994;Yankulov and Bentley, 1997), Oct transcription factors (Inamoto et al, 1997), p53 (Ko et al, 1997), retinoic receptor alpha (RARa) (Rochette-Egly et al, 1997), estrogen receptor alpha (ERa) (Chen et al, 2000), and pRb (Wu et al, 2001).…”
Section: Cdks Associated With the Rnap II Transcription Machinerymentioning
confidence: 99%
“…Transcriptionally active TFIIH (`holo TFIIH') requires association of`core TFIIH' with the trimeric CDK7-cyclin C-MAT1 kinase (Svejstrup et al, 1995;Coin and Egly, 1998). TFIIH performs at least three critical functions in RNAP II transcription; (i) it mediates ATP-dependent promoter DNA opening (Wang et al, 1992;Holstege et al, 1997) through its 3 0 -5 0 helicase activity provided by the XBP (ERCC3) subunit (Guzder et al, 1994;Tirode et al, 1999), (ii) phosphorylates the RNAP II CTD through its CDK7 kinase subunit (Feaver et al, 1994;Roy et al, 1994;Serizawa et al, 1995;Shiekhattar et al, 1995) during the transition from transcription initiation to elongation (Dahmus, 1994(Dahmus, , 1996, and (iii) suppresses transcription arrest of early RNAP II elongation complexes (Spangler et al, 2001).…”
Section: Cdks Associated With the Rnap II Transcription Machinerymentioning
confidence: 99%
“…Phosphorylation of RNAPII is an important rate limiting step for e cient elongation of RNAPII transcripts shortly after initiation (Dahmus, 1996). CDK7 and its yeast homolog Kin28 are subunits of the basal transcription factor TFIIH (Feaver et al, 1994;Roy et al, 1994). CDK8 and its yeast homolog Srb10 are components of the RNAPII holoenzyme (Maldonado et al, 1996;Rickert et al, 1996;Tassan et al, 1995).…”
Section: Introductionmentioning
confidence: 99%